DARI HIP HOP KE POP: MENELISIK ESTETIKA DALAM VIDEO KLIP BANGTAN BOYS (BTS) - Agung, Lingga; Rosandini, Morinta; Prasetya, Shyavira (Universitas Mercu Buana, 2022)
This research aims to see how the aesthetic changes in the two music video of Bangtan Boys (BTS), “No More Dream” (2013) and “Permission to Dance” (2021). Aesthetic changes are always releted to the cultural changes, and therefore it is interesting to investigate more deeply. This research collects qualitative data from books, journals, and especially from the two music video above. To see the aesthetic changes, we use the post-colonial theory of Homi K. Bhabha which is relevant dor this research. From the research that has been done, the two BTS music video take the aesthetic idioms of Western (United States) pop culture. Changes in aesthetics actually only follow global trends (United States). We don't find a solid South Korean cultural 'visual cue' in the two music video. However, 'Korean Style', 'K-Pop Aesthetics', 'BTS looks', and so on were born because the two music video are mimicry and hybrids that have succeeded in integrating and hegemonizing Western (United States) pop culture idioms into K-Pop culture idiom.